Analisis Spektroskopi Inframerah Transformasi Fourier dan Kemometri Boraks pada Bakso - Anwar, Yelfi; Hilaly , Kamelia Nur; Rahmatika , Fifi; Haryanza , Larasati Sekar; Cahyani , Sutta Dharma; Zanzadeh , Muhammad; Zahra , Nisfa; Putri , Fransiska Monika; Sinaga , Michaela Theresia; Kusuma , Falla; Sari , Kayla Firda; Ayuningtyas, Rizka; et al. (Inspirasi: Jurnal Pengabdian Masyarakat, 2025)
Bakso is an Indonesian specialty that is favored by many people. Meatballs are in the form of spheres or other shapes obtained from a mixture of animal meat which can be beef or chicken, tapioca flour, and other food additives (BTP). Borax is a dangerous chemical compound that is often misused by producers in meatball processing. Borax is commonly used as a preservative, lubricant or cleaning agent. Borax is a B3 (Toxic and Dangerous Substance) which is toxic. Consumption of food containing borax is not directly harmful, but borax will be absorbed cumulatively in the consumer's body. The purpose of this activity is to introduce students and the general public to infrared spectrophotometer tools and educate about the dangers of borax content in meatballs. The method of implementing the introduction of the infrared spectrophotometer tool and the danger of borax content in meatballs was carried out using a zoom meeting. The activity was accompanied by the administration of pre-test and post-test questionnaires with an average understanding of the pre-test percentage of 83.80% to 91.80% during the post test. From these results, it can be said that the webinar that has been carried out can provide benefits in the form of knowledge insights to the community.